The Usefulness of Mandibular Ramus as an Indicator in Sex Differentiation Using 3D Reconstructed Computed Tomography - Sahar Sh. Kadhim; Ahlam Ahmed Fatah (College of Dentistry/ University of Baghdad, 2016)
Background: Determination of sex from an unknown human bone is an important role in forensic and anthropology field. The mandible is the largest and hardest facial bone, that commonly resist postmortem damage and forms an important source of information about sexual dimorphism. Mandibular ramus can be used to differentiate between sexes and it also expresses strong univariate sexual dimorphism. This study was undertaken to assess the usefulness of mandibular ramus as an aid in sex differentiation using CT scanning among Iraqi population. Materials and methods: 3D reconstructed computed tomography scanning of 140 Iraqi Arab subjects, (7 0 males and 70 females) were analyzed with their age range from 20-60 years old. The linear measurements were located and marked on axial and sagittal sections including right and left sides of the mandible. Results: For the all measurements for sexes the mean value for male were highly significant than female with (P= value < 0.001).A receiver operating characteristic curves was obtained for each variable to observe their overall performance in sex determination. The area of maximum mandibular ramus height was found to be the best parameter according to ROC analysis to establish the diagnosis of male (ROC=0.952cm for both unilateral and bilateral measurements). Age showed no statistical difference in the current study. Conclusion: 3D reconstructed computed tomography scanning plays an important role as a diagnostic method for analyzing the linear measurements of the mandibular ramus in sex differentiation. Sex determination for isolated part of the skull (e.g. mandible) could be achieved, instead of complete skull, and the highest accuracy in sex determination can be obtained whether complete or part of mandible is available for examination